Telerehabilitation Intervention in Patients with COVID-19 after Hospital Discharge to Improve Functional Capacity and Quality of Life. Study Protocol for a Multicenter Randomized Clinical Trial. - Pastora Bernal, Jose Manuel; Estebanez Pérez, María José; Molina-Torres, Guadalupe; García López, Francisco José; Sobrino Sanchez, Raquel; Martín-Valero, Rocío (MDPI, 2021)
COVID-19 can cause important sequels in the respiratory system and frequently presents loss of strength, dyspnea, polyneuropathies and multi-organic affectation. Physiotherapy interventions acquire a fundamental role in the recovery of the functions and the quality of life. Regarding the recovery phases after hospital discharge, the current evidence available is very preliminary. Telerehabilitation is presented as a promising complementary treatment method to standard physiotherapy. The main objective of this research is to evaluate the effectiveness of a personalized telerehabilitation intervention after discharge from hospital for the improvement of functional capacity and quality of life compared to a program of health education and/or care in a rehabilitation center. As secondary objectives, to identify the satisfaction and perception of patients with the telerehabilitation intervention and the presence of barriers to its implementation, as well as to evaluate the cost-effectiveness from the perspective of the health system. This study protocol will be carried out through a single blind multicenter randomized clinical trial in the south of Spain. We hypothesize that the implementation of a telerehabilitation program presents results not inferior to those obtained with the current standard intervention. If the hypothesis is confirmed, it would be an opportunity to define new policies and interventions to address this disease and its consequences. Trial registration NCT04742946.
Keywords: Rehabilitación - Innovaciones tecnológicas; COVID-19 - Complicaciones y secuelas; Fisioterapia; COVID-19; COVID-19 sequelae; Confinement; Discharge from hospital; Physiotherapy; Telerehabilitation